To study the awareness of needle stick injuries among healthcare workers in an area select of tertiary care hospital - Latika; Ridhi Suri; Dahiya, Pushpa (Asian Journal of Medical Sciences, 2024)
Background: Needle stick injuries, or NSIs, refer to injuries produced by several types of needles, including hypodermic needles, blood collection needles, intravenous stylets, and needles used for connecting components of intravenous administration systems. Aims and Objectives: The study aimed to study the awareness of NSIs among healthcare workers (HCWs) in a selected area of a tertiary care hospital. Materials and Methods: A cross-sectional study was undertaken within the department of obstetrics and gynecology (OBG). The study’s target group was all HCWs of varied experience levels (n=272). This study employed a meticulously crafted questionnaire in the English language. The survey includes 22 items covering a variety of NSI-related topics. Subgroup analysis was conducted using the Pearson Chi-square test. Results: It was found that most of them were in the 20–30 age group (75%), the majority were females (72%), unmarried (61%), and from an urban background (85%). Almost all the participants (96%) were aware that NSIs are preventable. Similarly, 90% of the participants were aware that NSIs may cause the transmission of diseases, and 77% of the participants reported that they have training on biomedical waste management and its disposal. About 74% of the respondents stated that they had been exposed to NSIs. Conclusion: This study sheds light on the awareness levels and experiences of HCWs regarding NSIs in the OBG department. While a high level of awareness was observed, the study identified areas for improvement in the implementation of preventive measures, reporting practices, and post-exposure management.